2004
DOI: 10.1097/01.tp.0000141363.81600.0d
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Microangiopathy after Allogeneic Blood and Marrow Transplantation Is Associated with Dose-Intensive Myeloablative Conditioning Regimens, Unrelated Donor, and Methylprednisolone T-Cell Depletion

Abstract: Avoidance of high-intensity conditioning regimens may decrease the incidence of allogeneic BMT-associated TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
1
25
1
1
Order By: Relevance
“…death in 1 out of 19 (5%), 33 2 out of 13 (15%), 14 none of six (0%), 34 and 4 out of 19 (21%) patients. 15 On the other hand, in this study, TMA was a contributing cause in 15 out of 27 (56%) patients who died after being diagnosed with TMA, which revealed the clinical impact of TMA in patients with acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…death in 1 out of 19 (5%), 33 2 out of 13 (15%), 14 none of six (0%), 34 and 4 out of 19 (21%) patients. 15 On the other hand, in this study, TMA was a contributing cause in 15 out of 27 (56%) patients who died after being diagnosed with TMA, which revealed the clinical impact of TMA in patients with acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] The reported incidence of TMA varies from 0.5 to 76%. [13][14][15][16][28][29][30][31][32][33][34] A recent literature review identified 447 (8.2%) cases of TMA, with a median mortality of 75% within 3 months of the diagnosis. 35 The large variability in the published incidence is due to the fact that there are no uniformly accepted diagnostic criteria for this clinical syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Although its etiology and pathogenesis have not been fully clarified, endothelial damage induced by multiple factors, such as conditioning regimens, GVHD, immunosuppressants and infection, contributes to its development. [6][7][8][9][10][11][12][13][14][15] Management of TAM is supportive, and withdrawal or decreasing the dose of calcineurin inhibitors is suggested as the first step in the treatment. 4,10 Severe diarrhea is a serious symptom after allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Thrombotic microangiopathy is characterized by systemic or intrarenal platelet aggregation and a microangiopathic hemolytic anemia, with red blood cell (RBC) fragmentation and a negative direct antiglobulin test. Increased platelet consumption leads to thrombocytopenia.…”
mentioning
confidence: 99%